Evaluating leadership development in a changing world? Alternative models and approaches for healthcare organisations. Issue 2 (15th March 2023) - Joseph-Richard, Paul; McCray, Janet
ABSTRACT: Internationally, healthcare is undergoing a major reconfiguration in a post-pandemic world. To make sense of this change and deliver an integrated provision of care, which improve both patient outcomes and satisfaction for key stakeholders, healthcare leaders must develop an insight into the context in which healthcare is delivered, and leadership is enacted. Formal leadership development programmes (LDPs) are widely used for developing leaders and leadership in healthcare organizations. However, there is a paucity of rigorous evaluations of LDPs. Existing evaluations often focus on individual-level outcomes, with limited attention to long-term outcomes that might emerge across team and organizational levels. Specifically, evaluation models that have been closely associated with or rely heavily on qualitative methods are seldom used in LDP evaluations, despite their relevance for capturing unanticipated outcomes, investigating learning impact over time, and studying collective outcomes at multiple levels. The purpose of this paper is to review the potential of qualitative models and approaches in healthcare leadership development evaluation. This scoping review identifies seventeen evaluation models and approaches. Findings indicate that the incorporation of qualitative and participatory elements in evaluation designs could offer a richer demonstration and context-specific explanations of programme impact in healthcare contexts.